Serum Lipids and the Risk of Gastrointestinal Malignancies in the Swedish AMORIS Study. (30th August 2012) - Wulaningsih, Wahyu; Garmo, Hans; Holmberg, Lars; Hammar, Niklas; Jungner, Ingmar; Walldius, Göran; Van Hemelrijck, Mieke
Abstract : Background . Metabolic syndrome has been linked to an increased cancer risk, but the role of dyslipidaemia in gastrointestinal malignancies is unclear. We aimed to assess the risk of oesophageal, stomach, colon, and rectal cancers using serum levels of lipid components. Methods . From the Swedish Apolipoprotein Mortality Risk (AMORIS) study, we selected 540, 309 participants (> 20 years old) with baseline measurements of total cholesterol (TC), triglycerides (TG), and glucose of whom 84, 774 had baseline LDL cholesterol (LDL), HDL cholesterol (HDL), apolipoprotein B (apoB), and apolipoprotein A-I (apoA-I). Multivariate Cox proportional hazards regression was used to assess glucose and lipid components in relation to oesophageal, stomach, colon, and rectal cancer risk. Results . An increased risk of oesophageal cancer was observed in persons with high TG (e.g. HR: 2.29 (95% CI: 1.42–3.68) for the 4th quartile compared to the 1st) and low LDL, LDL/HDL ratio, TC/HDL ratio, log (TG/HDL), and apoB/apoA-I ratio. High glucose and TG were linked with an increased colon cancer risk, while high TC levels were associated with an increased rectal cancer risk. Conclusion . The persistent link between TC and rectal cancer risk as well as between TG and oesophageal and colon cancer risk in normoglycaemic individuals may imply their substantiality in gastrointestinal carcinogenesis.